The Museum of Light and the Epoch of Disappearance - John W.P. Phillips (Media Theory, 2019)
The bleak announcement to Paul Virilio’s La vitesse de libération [Open Sky, 1997] forecasts a final dawn: “one day the day will come when the day won’t come” (1997: iii). The motif of the dawn in Virilio’s writing brings his focus to bear on the phenomena of rapid transport and electronic transmission technologies as they come to reproduce and in principle to replace the spatial and temporal environment of bodies illuminated by solar optics. In this article, I raise a question concerning the experiential sphere of morality, consciousness and community in Virilio’s explanation of an epoch increasingly dominated by these technologies. If Virilio is correct, we are in a transition towards the final epoch of humanity, governed by a quasi-theological media environment, and characterised by an experience of disappearance that was entirely novel to the twentieth century. The article assesses Virilio’s account of the paradoxical emergence from the ruins of the urban architecture of a city characterised by the phenomena of disappearance and substitution: a city that functions as the museum of the phenomena it supplants.